Exploring the Contemporary Challenges of Urbanization and the Role of Sustainable Urban Development: A Study of Lagos City, Nigeria - Auwalu, Faisal Koko; Bello, Muhammed (Journal of Contemporary Urban Affairs, 2023)
As urbanization accelerates, sustainable approaches are necessary to counter the adverse environmental impacts. The study investigates the multifaceted challenges of Lagos City due to urbanization and evaluates the effectiveness of sustainable urban development in tackling these problems. It employed a mixed-methods approach to provide informed decisions for liveable urban environments. Census data, satellite imagery, interviews, surveys, and focus group discussions provided a comprehensive understanding of Lagos’s urbanization and its effects. Findings reveal pressing problems such as housing shortages, infrastructure strain, traffic congestion, waste management difficulties, and socio-economic disparities in Lagos City. Local authorities and NGOs have implemented sustainable urban development initiatives, including transport upgrades, green space promotion, waste management, and housing solutions. Such case studies have revealed various interventions, such as informal settlement transformation, renewable energy integration, and urban regeneration. However, persistent issues still exist due to the city’s urbanization. Therefore, Integrated urban planning, inclusivity in policy-making, and technological advances are essential for tackling these challenges. The findings contribute to the academic discourse by providing insights into Lagos City’s urbanization and practical implications for sustainable urban development. It also highlights the need for comprehensive strategies to build a prosperous, equitable, and eco-friendly city.